Sosialisasi dan Pelatihan Penggunaan Aplikasi SMART Guna Mendukung Tertib Administrasi di Lingkungan Rukun Tetangga - Rahmatulloh, Alam; Rianto, Rianto; Gunawan, Rohmat; Rizal, Randi (UN PENMAS (Jurnal Pengabdian Masyarakat untuk Negeri), 2024)
Rukun Tetangga (RT) is a community organization formed through deliberation and consensus of the local community to maintain harmony in life. Managing population administration at the RT level is one of the responsibilities of the RT Head. Population administration needs to be managed well, because population data is a basic statistical source in making various policies. In order to create administrative order in managing population data, in this service activity, socialization and training on the use of the SMART application (Sistem Informasi Manajemen Administrasi Rukun Tetangga) is carried out. Residents of RT 04 RW 07 Arjasari Village, Leuwisari District, Tasikmalaya Regency are partners in this service activity. There are several stages carried out in this service activity, including: stage 1 initial preparation, stage 2 main program, stage 3 closing the activity. Socialization and training on using the SMART application was carried out at partner locations on Friday 15 September. This application is expected to facilitate and make it easier for RT Heads and residents to complete population data and support orderly administration.